A comparison of English, Acehnese, and Indonesian monophthongs - Masykar, Tanzir; Pillai, Stefanie; Hassan, Roshidah (Universitas Syiah Kuala, 2023)
Foreign language learners tend to approximate the quality of non-native vowels to their existing vowel systems. This phenomenon becomes more complicated in learners who already have more than one vowel system in their linguistic repertoire. When learning English, Acehnese-Indonesian speakers are likely to already have two other vowel systems, Acehnese and Indonesian. Thus, the quality of English monophthongs produced by these speakers may resemble the equivalent of Acehnese and Indonesian monophthongs. This study compares the quality of English monophthongs to equivalent Acehnese and Indonesian monophthongs produced by Acehnese-Indonesian speakers. A total of 29 students from a Modern Islamic Boarding School in Aceh participated in this study. The students were recorded producing nine English, 11 Acehnese, and seven Indonesian monophthongs embedded in target words produced in a carrier sentence. The study found that the nine English monophthongs were produced at an approximate quality to either Acehnese and/or Indonesian monophthongs. In some cases, the English vowel was produced similarly to both the equivalent vowels in Acehnese and Indonesian. In other cases, the English vowel was produced more similarly to either Acehnese or Indonesian. The findings of this study provide insights into how Acehnese-Indonesian learners filter English vowels through their existing L1 and L2 sounds and allow for a better understanding of this phenomenon via existing conceptual models. The findings also point to the often-ignored influence of other languages in a speakers repertoire on the learning and production of a new language.